Le fratture diafisarie di omero in età pediatrica - Casaburi, A.; Lamberti, D.; Busiello, T.; Sorrentino, B.; Siesto, V.; Guida, P. (Lo Scalpello - Journal, 2018)
HUMERAL SHAFT FRACTURES IN THE PAEDIATRIC AGEHumeral shaft fractures are uncommon in children. They occur with bimodal distribution, presenting peaks in thefirst and third childhood. The treatment differs according to age and fracture complexity. Most of them generallyoccur at the medial third of humeral bone, below the distal insertion of the deltoid. The management of minimallydislocated fractures is non-surgical, thanks to children bone remodelling capacity. Surgery is indicated in openfractures, multiple trauma, compartment syndromes and inadequate closed reduction. The elastic intramedullarynailing is the most used therapeutic approach. It is a minimally invasive, simple technique with a very lowcomplication rate.